Application of half-raised bed root-zone restriction on protected cultivation grapes in south China - JIA Hui-juan; HUA Xiang-hong; TENG Yuan-wen; HE Feng-jie; LU Ru-guo (浙江大学学报. 农业与生命科学版)
Root-zone restriction of half-raised bed cultivation was applied to four grape varieties (Fujiminori, Kyoho, Summerblack and Jinshouzhi) in south China, and its effects on grape quality under protected cultivation were studied. The results showed that using the high-density compacted soil of 15-20 cm below soil surface as a natural buffer zone, could well play the role of restricting root growth, and the root-zone restriction could improve the grape inner, visual and nutrition quality. The ratio of total soluble sugar (TSS) to total acidity (TA) was raised at the four varieties, and the anthocyanin and total phenolic contents increased at the three cultivars (Fujiminori, Kyoho and Summerblack) by root-zone restriction system. Besides the mass of Fujiminori berry was reduced significantly, that of the other three cultivars had not significant effect by root-zone restriction of halfraised bed cultivation. These results suggest that the technique of root-zone restriction of half-raised bed cultivation in south China has a positive effect under facility cultivation condition.